The Rising Trend of Human Smuggling: Causes and Remedies: An Analytical Study of the Society of District Kasur in the Light of Islamic Shariah Dr. Irfan  - Dr. Irfan; Dr. Zahoor Ullah Al-Azhari (jihat-ul-islam, 2024)
This research article, "The Rising Trend of Human Smuggling: Causes and Remedies (An Analytical Study of the Society of District Kasur in the Light of Islamic Shariah)," addresses one of the most pressing issues facing modern societies: human Smuggling. This illicit trade, a contemporary form of slavery, has severely undermined social fabric and humanity’s shared values. Economic hardship, natural disasters, civil unrest, and wars are primary drivers of human Smuggling, with Pakistan being significantly affected. Each year, thousands of Pakistanis attempt illegal migration, often falling victim to Smugglers. The study aims to identify the root causes of human Smuggling, understand why Pakistani youth resort to illegal migration, and explore solutions through Islamic teachings. The research questions focus on the fundamental causes of human Smuggling, the compulsion behind illegal migration, and the perspective of Islamic Shariah on human Smuggling and Smugglers. By examining these issues, the study seeks to propose effective measures to curb human Smuggling, raise awareness about legal actions against Smugglers, and emphasize the sanctity of human life in Islam. The ultimate goal is to reduce the prevalence of human Smuggling through timely and effective interventions